The Amazonian kambô frog Phyllomedusa bicolor (Amphibia: Phyllomedusidae): Current knowledge on biology, phylogeography, toxinology, ethnopharmacology and medical aspects - Nogueira, Thais A. C.; Kaefer, Igor Luis; Sartim, Marco A.; Pucca, Manuela B.; Sachett, Jacqueline; Barros, André L.; Júnior, Moysés B. A.; Baía-da-Silva, Djane C.; Bernarde, Paulo S.; Koolen, Hector H. F.; Monteiro, Wuelton M. (Frontiers in Pharmacology, 2022)
The amphibian species Phyllomedusa bicolor (Phyllomedusidae), popularly known as giant leaf frog, kambô, or sapo, is an iconical tree frog from the Amazon that has high relevance for some of the indigenous communities that live in this region. This species produces a white-colored poisonous secretion rich in bioactive peptides used in purification rituals of the body, to bring luck to hunters, to increase stamina, and used for healing purposes. The biological effects observed in the first studies with indigenous communities aroused the fascination of researchers, who over the last six decades have been studying the detailed chemical composition, as well as the potential pharmacological applications of its constituents. Moreover, recently, kambô has been increasingly used in large urban centers, especially in clinics that use it as an alternative therapy and for religious purposes. Given this fact, indigenous communities and health agents fear the misuse of kambô, or that inappropriate species are used, which can result in health complications or even death of users. Thus, considering that the literature on the subject is sparse, and in some cases biased due to conflicts of interest, this article seeks to bring a transdisciplinary review that integrates knowledge about the biology of P. bicolor, ethnoknowledge about the ritual of kambô, the chemistry, and pharmacology of the secretion of this species, as well as medical aspects of the indiscriminate use of kambô. In addition, this article seeks to bring a critical view, as well as shed light on perspectives on the future of research related to kambô.